2019
DOI: 10.1111/clr.13499
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and biological complications after implantoplasty—A systematic review

Abstract: Objectives Implantoplasty, that is, the mechanical modification of the implant, including thread removal and surface smoothening, has been proposed during surgical peri‐implantitis treatment. Currently, there is no information about any potential mechanical and/or biological complications after this approach. The aim of the current review was to systematically assess the literature to answer the focused question “Are there any mechanical and/or biological complications due to implantoplasty?”. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 46 publications
2
49
0
2
Order By: Relevance
“…That fibroblasts respond differently according to substrate roughness is already known [17,18,27]. However, this has only been shown on surfaces prepared in laboratories with delicate equipment and procedures impossible to replicate intraorally in patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…That fibroblasts respond differently according to substrate roughness is already known [17,18,27]. However, this has only been shown on surfaces prepared in laboratories with delicate equipment and procedures impossible to replicate intraorally in patients.…”
Section: Discussionmentioning
confidence: 98%
“…Implantoplasty is above all performed to counter microbial challenges, and its impact on preventing bacterial recolonization and facilitating removal of bacterial colonization is considered pivotal to healing and homeostasis of peri-implant health following implantoplasty treatment in response to peri-implantitis challenges. So far in vitro studies on implantoplasty have focused on surface roughness [8][9][10], heat generation [11][12][13], and fracture resistance [14,16,17]. This study provides some new insights on the soft tissue component following experimental implantoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far in vitro studies on implantoplasty have focused on surface roughness, 8,9,10 heat generation, 11,12,13 and fracture resistance. 14,16,17 This study Although efforts were made to collect the experimental implantoplasty debris, particles may have been lost as aerosols during drilling. The fibronectin imaging was not possible to perform with standardized laser strength in all cases, which may have influenced the subsequent arbitrary quantification.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Fracture resistance has also been the focus of in vitro studies 16 , but according to a recent systematic review no fractures following implantoplasty have been reported in the literature. 17 A possible advantage of implantoplasty in addition to facilitated oral hygiene is a potential improvement of the soft tissue adaptation to the dental implant. An ideal implant surface should impede bacteria and biofilm growth and adhesion while at the same time allow rapid connective tissue attachment.…”
Section: Introductionmentioning
confidence: 99%